Nanoencapsulation of anthocyanins based on pectin and lysozyme: a new technological approach to increase the physicochemical stability of phenolic compounds - Rosales, Thiécla Katiane Osvaldt (2022)
Anthocyanins are sensitive flavonoid pigments and are widely distributed in nature. Currently, these phenolic compounds are being extensively researched due to intense interest in their beneficial properties. Due to their functionalities, they can be added to food products for natural coloring, functional ingredients, and in the development of nutritional supplements. The consumption of these antioxidant pigments can be a strategy for reducing the risk of developing chronic non-communicable diseases in the population. However, the molecular instability of these compounds limits their technological use. Nanoencapsulation based on pectin and lysozyme is considered a viable option to stabilize it and enable this inclusion. Thus, the present thesis had as primary objectives: 1) to develop a new methodology for nanoencapsulation of anthocyanins based on pectin and lysozyme; 2) to characterize physical and chemically the nanostructures with encapsulated anthocyanins; 3) to evaluate stability in different pH and temperature ranges; 4) to observe the stability of nanostructures and the preservation of intact anthocyanins in a simulated digestion system; 5) to analyze the effect on cell viability, cytotoxicity and in vitro uptake in human cells; 6) to discuss possible biological effects and feasibility for inclusion in food products. Mathematic models were used for optimization parameters. To characterize the nanostructures, analysis of Dynamic Light Scattering, Scanning Microscopy, Differential Scanning Calorimetry, Fourier Transforms Infrared Spectral, and Encapsulation Efficiency were performed. To analyze the stability different pH titrations and temperatures of 4 °C, 25 °C, and 40 °C were observed, simulated in vitro digestion (INFOGEST) was evaluated, and the effect in cells two- and three-dimensional cell models were used to determine viability, toxicity, and cellular incorporation. The nanostructures were formed by a complex network of molecular self-organization. The results showed that the formed nanostructures have adequate physicochemical characteristics, an average size of 190 nm, spherical and homogeneous morphology, a Zeta Potential of about -30, and an efficiency of encapsulation of 79%. The nanostructures were stable in different pH and temperature ranges, simulating storage. In the gastrointestinal system, anthocyanins were gradually released, and they maintained stable colloid characteristics in the intestine. The viability of cells treated with nanoparticles was maintained, they had no cellular toxicity, and the nanostructures successfully absorbed the nanostructures in cells, as observed by microscopy. The pectin covered the nanostructures, while lysozyme provide internal stability, and anthocyanin was effectively encapsulated. Future in vivo experiments are indicated to analyze the bioavailability. Pectin-based nanostructures were effective in maintaining stability and for prospecting inclusion in food products and supplements.